PROFILE OF LEPROSY IN CHILDREN FROM 2014-2018 IN DR. SOETOMO GENERAL HOSPITAL SURABAYA - Billy Jiwandono (Jurnal Kesehatan dan Kedokteran, 2022)
Type 2 Diabetes Melitus is a metabolic disorder that is marked by the rise in blood sugar due to a decrease in insulin secretation by pancreatic beta cells and insulin function ordisorders (insulin resistance). Risk factors of diabetes mellitus type 2, namely age, gender, obesity, hypertension, genetics, diet, smoking, alcohol, lack of activity. Patients with Diabetes Melitus are required to implement a complex management disease such as nutritional therapy, physical exercise, glucose controlling, and pharmalogical therapy. Diabetes melitus can cause complications and symptoms that interferes activities, the implications of Diabetes Melitus be a stressor that cause stress, stressor can be controlled by coping mechanism. Mechanism coping is an active process in which the use of resources from the private and develop new behavior that aims to grow the strength of an individual, even an emergency reduce the impact of stress in life, disability incurred. Coping mechanism is adaptive and maladaptive. This aims study to explore coping strategies of patients with type 2 diabetes melitus in internal medice polyclinic Cipto Mangunkusumo Hospital, Jakarta. This study used quantitative description. Research result shows that patient who use adaptive coping 38 people (73%), whereas the use coping maladaptive 14 people (27%), then it can be concluded that diabetes mellitus patients more coping mechanisme malaadaptive.